Ce Doping Boosts the Thermo‐ and Photocatalytic Oxidation of CO at Low Temperature in TiZrO4 Solid Solutions. Issue 14 (19th June 2021) - Tang, Panjuan; Livraghi, Stefano; Giamello, Elio; Garroni, Sebastiano; Malfatti, Luca; Agnoli, Stefano
Abstract: Palladium nanoparticles supported on zirconium titanate with cerium doping up to 10% molar (Ce‐ZT) are prepared by a facile impregnation method and characterized by several techniques. Due to electronic effects, the amount of Ce cations in a reduced oxidation state, i.e., Ce(III), is surprisingly high, more than 50% of the total cerium amount. The Pd decorated Ce‐ZT nanoparticles exhibit excellent catalytic activity in the low temperature oxidation of CO. The amount of Pd and Ce concentration results to be the key parameters controlling the catalytic performance. The best activity is observed in the sample with the highest Ce doping (10% molar) and a nominal Pd loading of 2% w/w, which exhibits an outstanding turnover frequency of 0.1 s −1 at 45 ° C. Moreover, the CO conversion remains unchanged at 100% for 24 h at 50 ° C, or for several successive light‐off experiments up to 120 ° C, demonstrating excellent long‐term stability. Light irradiation is shown to further improve the catalytic performance allowing to reach the same catalytic activity of dark conditions at a temperature that is 20–40 ° C lower. Electron paramagnetic resonance spectroscopy experiments indicate that Pd nanoparticles and Ce(III) ions can trap electrons favoring charge separation and formation of superoxide species, therefore enabling photocatalysis. Abstract : Palladium nanoparticles decorating ceria doped ZrTiO4 are outstanding catalysts for the CO oxidation at low temperature, reaching a turnover frequency of 0.1 s ‐1 at 45 °C. Under visible light irradiation, the catalytic activity is further improved by the presence of Ce(III) ions that can easily trap photoexcited electrons and form reactive superoxide species, as demonstrated by electron paramagnetic resonance experiments.